2010
DOI: 10.1111/j.1532-7078.2009.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Signals of Familiarity and Recency in the Infant Brain

Abstract: Electrophysiological work in nonhuman primates has established the existence of multiple types of signals in the temporal lobe that contribute to recognition memory, including information regarding a stimulus's relative novelty, familiarity, and recency of occurrence. We used high-density event-related potentials (ERPs) to examine whether young infants represent these distinct types of information about previously experienced items. Twenty-four different highly familiar and initially novel items were each repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 50 publications
(136 reference statements)
2
31
0
Order By: Relevance
“…However, significant changes in the amplitude of the LSW are routinely observed across repeated stimulus presentations or with increased familiarity. Thus, the LSW is believed to be associated with stimulus encoding and infant recognition memory (de Haan & Nelson, 1999; Reynolds, Guy, & Zhang, 2011; Nelson & Collins, 1991; Nelson & Collins, 1992; Snyder, 2010; Snyder, Webb, & Nelson, 2002; Snyder et al, 2010; Webb, Long, & Nelson, 2005; Wiebe et al, 2006). From 4 to 12 months, infants become increasingly more likely to demonstrate LSW correlates of recognition of a fully processed stimulus in response to previously encountered stimuli (Nelson & Collins, 1992; Nelson & deRegnier, 1992; Reynolds & Richards, 2011).…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 99%
See 1 more Smart Citation
“…However, significant changes in the amplitude of the LSW are routinely observed across repeated stimulus presentations or with increased familiarity. Thus, the LSW is believed to be associated with stimulus encoding and infant recognition memory (de Haan & Nelson, 1999; Reynolds, Guy, & Zhang, 2011; Nelson & Collins, 1991; Nelson & Collins, 1992; Snyder, 2010; Snyder, Webb, & Nelson, 2002; Snyder et al, 2010; Webb, Long, & Nelson, 2005; Wiebe et al, 2006). From 4 to 12 months, infants become increasingly more likely to demonstrate LSW correlates of recognition of a fully processed stimulus in response to previously encountered stimuli (Nelson & Collins, 1992; Nelson & deRegnier, 1992; Reynolds & Richards, 2011).…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 99%
“…Snyder and colleagues (Snyder, Garza, Zolot, & Kresse, 2010) investigated potential neural mechanisms underlying the LSW and infant recognition memory. Six-month-old infants were tested in a procedure which allowed for the analysis of recency and familiarity effects.…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 99%
“…Other research has confirmed that Nc as well as early NSW reflect responses to novel stimuli (e.g., Ackles, ; Quinn, Westerlund, & Nelson, ; Wiebe et al, ). Interestingly, studies employing stimuli that infants are highly familiar with, for example, the mother's face or a favorite toy, have demonstrated greater Nc amplitude to these stimuli than to unfamiliar ones (e.g., Carver et al, ; Snyder, Garza, Zolot, & Kresse, ).…”
Section: The Contribution Of Physiological Studiesmentioning
confidence: 99%
“…Snyder et al () argue that the late slow wave reflects both recency and familiarity effects. These effects can be attributed to neuronal activity in the perirhinal cortex (e.g., Yassa & Stark, ).…”
Section: The Contribution Of Physiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation